2012
DOI: 10.1007/s10995-012-0962-6
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Financial and Educational Interventions on Maternity Care: Results of Cluster Randomized Trials in Rural China, CHIMACA

Abstract: To report on the design and basic outcomes of three interventions aimed at improving the use and quality of maternity care in rural China: financial interventions, training in clinical skills, and training in health education. Community-based cluster randomized trials were carried out in one central and two western provinces between 2007 and 2009: (1) financial interventions covered part of women's costs for prenatal and postnatal care, (2) training of midwives in clinical skills was given by local maternity c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
37
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(37 citation statements)
references
References 9 publications
0
37
0
Order By: Relevance
“…One controlled before-and-after study (n = 425,708 women) and one cross-sectional study (n = 2,267 women) found no differences in uptake of antenatal care [34,40]. A retrospective area study (n = 20,133 women) of Nigeria’s SURE-P programme found no increase in receipt of any antenatal care [44] and a cluster RCT (n = 592 women) on the CHIMACA programme in China found no evidence of effect on number of antenatal contacts women received [43]. …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…One controlled before-and-after study (n = 425,708 women) and one cross-sectional study (n = 2,267 women) found no differences in uptake of antenatal care [34,40]. A retrospective area study (n = 20,133 women) of Nigeria’s SURE-P programme found no increase in receipt of any antenatal care [44] and a cluster RCT (n = 592 women) on the CHIMACA programme in China found no evidence of effect on number of antenatal contacts women received [43]. …”
Section: Resultsmentioning
confidence: 99%
“…A cluster RCT (n = 592 women) of the CHIMACA programme in China (which offered payments to women if they attended antenatal care), using 104 towns in five counties as clusters, found evidence that the programme increased caesarean section rates, which were 67.1% among intervention clusters and 56.0% among control clusters [43]. A controlled before-and-after study (n = 5,903 women) of India’s Janani Suraksha Yojana found no evidence of effect on caesarean section rates [36], however a cross-sectional study (n = 2,267) found rates increased in one state (where it was 15%) with no evidence of effect in another state [40].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations